Integrative economic ethics foundations of a civilized market economy - Ulrich, Peter 1948- (Cambridge University Press, 2008)
Integrative Economic Ethics is a highly original work that progresses through a series of rational and philosophical arguments to address foundational issues concerning the relationship between ethics and the market economy. Rather than accepting market competition as a driver of ethical behaviour, the author shows that modern economies need to develop ethical principles that guide market competition, thus moving business ethics into the realms of political theory and civic rationality. This book was in its fourth edition in the original German in 2008, this English translation of Peter Ulrich's development of a fresh integrative approach to economic ethics will be of interest to all scholars and advanced students of business ethics, economics, and social and political philosophy
Title from publisher's bibliographic system (viewed on 14 Jan 2016)
Keywords: Ethik; Wirtschaft; Economics / Moral and ethical aspects; Business ethics; Social ethics; Political ethics; Wirtschaftsethik